Parameterised verification of data-aware multi-agent systems - Belardinelli,F; Kouvaros,P; Lomuscio,A (2017)
We introduce parameterised data-aware multiagent systems, a formalism to reason about the temporal properties of arbitrarily large collections of homogeneous agents, each operating on an infinite data domain. We show that their parameterised verification problem is semi-decidable for classes of interest. This is demonstrated by separately addressing the unboundedness of the number of agents and the data domain. In doing so we reduce the parameterised model checking problem for these systems to that of parameterised verification for interleaved interpreted systems. We illustrate the expressivity of the formal model by modelling English auctions with an unbounded number of bidders on unbounded data.